Transforming Values: The Impact of Bogotá’s Public Trash Collection Service - Leitner, Julia (2015)
Mounds of garbage amassed on street corners, in front of houses. Bags splayed open, spilling onto the sidewalks, fi lling the city with stench. For three days, between December 18 and 20, 2012, trash piled up on the streets of Colombia’s capital city, a city of eight million residents. This period marked the handover of waste collection in Bogotá from private companies to public entities. For those who had ignored the previous months of debate on garbage collection, the problem was brought to the forefront, to the sidewalks, and a fetid phenomenon opened a discussion on environmental responsibility, social and political inclusion, private vs. public interests and the profi tability of garbage.